2000
DOI: 10.1002/(sici)1097-4644(20000201)76:2<181::aid-jcb2>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Presence of simian virus 40 sequences in malignant mesotheliomas and mesothelial cell proliferations

Abstract: Malignant mesotheliomas (MMs) are pleural-, pericardial-, or peritoneal-based neoplasms usually associated with asbestos exposure. Mesothelial cells are biphasic and may give rise to epithelial and sarcomatous MMs. In addition, benign or atypical proliferations of mesothelial cells may occur in response to many stimuli. There have been recent reports of simian virus 40 (SV40) DNA large T antigen (Tag) sequences in pleural MMs. To further understand the relationship between SV40, MMs, and mesothelial proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 21 publications
5
48
1
2
Order By: Relevance
“…Moreover, Shivapurkar et al (1999) detected SV40 in tumor cells from 57 of 118 mesotheliomas and in 1 of 75 nearby stromal cell areas microdissected from the same sections. This finding (which was independently confirmed by one of us, M Carbone, unpublished results) is of particular relevance because it is virtually impossible to produce a laboratory artifact of this kind.…”
Section: Sv40 Carcinogenesismentioning
confidence: 90%
“…Moreover, Shivapurkar et al (1999) detected SV40 in tumor cells from 57 of 118 mesotheliomas and in 1 of 75 nearby stromal cell areas microdissected from the same sections. This finding (which was independently confirmed by one of us, M Carbone, unpublished results) is of particular relevance because it is virtually impossible to produce a laboratory artifact of this kind.…”
Section: Sv40 Carcinogenesismentioning
confidence: 90%
“…However, these sequences were absent in matched adjacent lung tissue microdissected in parallel, making contamination an unlikely explanation. Furthermore, the SV40 sequences were present in both the pre-invasive and invasive component of the tumor cells, which indicated that SV40 is present beginning in the early stages of the neoplastic process (Shivapurkar et al, 1999).…”
Section: Sv40 and Human Mesotheliomamentioning
confidence: 95%
“…SV40 infection has been linked to a number of human cancers, including mesotheliomas, bone and brain tumors and lymphomas [47][48][49][50], although the mechanism involved is, as yet, controversial. In malignant mesothelioma (MM), a lethal neoplastic disease associated with asbestos exposure, SV40 DNA can be detected in 48% of MM patients [48]. However, there is no apparent link between SV40 and asbestos exposure suggesting that both viral and environmental factors contribute to the development of MM.…”
Section: Simian Virus 40mentioning
confidence: 99%